THE EFFECT OF FOREIGN OWNERSHIP ON THE FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES - Setiawan, Fanny Andriani; Kurniawati, Herni (Graduate Program of Universitas Tarumanagara, 2023)
This increase in competition forces companies to always make technological improvements and improvements in corporate governance so that there is harmony between the interests of managers, investor, and other stakeholders. The impact of foreign ownership in Indonesian companies as a form of GCG could increase the company's financial performance. This study aims to prove empirically how foreign ownership can affect the financial performance of a public manufacturing company. The financial report data used as the research sample is in the form of secondary data for companies listed on IDX from 2017-2020. This research was assisted by the software program EViews 10. The test results are that foreign ownership by both companies and foreign individuals/citizens has no positive effect on the financial performance of manufacturing companies listed on the IDX.